The Federal Democratic Republic of Ethiopia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
This Selected Issues paper reviews the extent to which growth in Ethiopia has translated into higher living standards. A key feature of the economic strategy has been an explicit commitment to poverty reduction and structural transformation. This is underpinned by the vision of a 'developmental state,' whereby a proactive public sector leads the development process and the private sector is oriented to support the development goals. The paper also identifies key bottlenecks hindering further broadening of growth across key sectors to reduce poverty, and highlights the main areas for policy action.